2022
DOI: 10.1109/access.2022.3225877
|View full text |Cite
|
Sign up to set email alerts
|

Wideband Self-Decoupling Dielectric Patch Filtennas With Stable Filtering Response

Abstract: Wideband self-decoupling of bandwidth-enhanced dielectric patch (DP) filtennas with stable filtering response are proposed in this letter. The TM101 and TE121 modes of the DP are combined to design a wideband antenna while its high-order TM111 mode is used to introduce an intrinsic upper radiation null, leading to a good filtering response. Sequentially, 1×2 DP filtennas have been taken as an example to verify that improving the isolation can keep the filtering performance of the filtenna array basically consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The adaptation of the radiator involves employing sophisticated techniques such as etching slot on the radiating element [99]- [110], incorporating an array of short-circuited metallic vias [111]- [116], introducing open stubs connected to radiating structure [117]- [122], exciting radiator with intrinsic radiation nulls [123]- [125], and parallelizing multiple resonating elements [126]- [128], all orchestrated to cancel the broadside radiation to attain a refined filtering response.…”
Section: A Evolved Radiatormentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptation of the radiator involves employing sophisticated techniques such as etching slot on the radiating element [99]- [110], incorporating an array of short-circuited metallic vias [111]- [116], introducing open stubs connected to radiating structure [117]- [122], exciting radiator with intrinsic radiation nulls [123]- [125], and parallelizing multiple resonating elements [126]- [128], all orchestrated to cancel the broadside radiation to attain a refined filtering response.…”
Section: A Evolved Radiatormentioning
confidence: 99%
“…Owing to high-order mode radiation and equivalent transmission line models, several radiators inherently possess radiation nulls, example of which include dielectric resonator antenna [123], cavity-backed antenna [124], and magnetoelectric dipole antenna [125]. Furthermore, parallelizing multiple resonating elements not only effectively broadens the bandwidth but also facilitates the creation of radiation nulls through multi-path coupling [126]- [128].…”
Section: A Evolved Radiatormentioning
confidence: 99%
“…ITH the rapid development of modern RF wireless communication systems, dielectric filtering antennas have been attracting increasing attention due to their low-loss and high-frequency-selectivity properties. Up to now, dielectric filtering antennas with various characteristics have been reported [1]- [17], such as dual-band/polarized performance, wide operational spectral range, reconfigurability, or omnidirectional radiation, among some others. It is found that all these engineered dielectric filtering antennas have the two following features: (i) adoption of a dielectric resonator antenna (DRA) or dense dielectric patch (DDP) as the radiator and (ii) co-integration of filtering capability obtained either from the feeding network or the own antenna structure.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, DRA [1]- [14] and DDP [15]- [17] structures have been widely used to realize dielectric filtering antennas, which both exhibit resonant characteristics. It is well known that the multiple modes of a DRA can be utilized to further extend its operational frequency range, while the DDP usually suffers from narrow-band characteristics.…”
Section: Introductionmentioning
confidence: 99%